Model Pondok Pesantren di Era Milenial - Shofiyyah, Nilna Azizatus; Ali, Haidir; Sastraatmadja, Nurhayati (BELAJEA: Jurnal Pendidikan Islam, 2019)
Pesantren is an oldest education system and considered as an Indonesian cultural product. Along with the change of era that experienced by Indonesian society, pesantren education also has development. With that background, compiler interested to distinguish various models of pesantren in this millennial era. The research method used study literature with a qualitative approach. From this research, can be concluded that the current globalization in the millennial era made its generation not far from the use of technology, the internet, social media and others. This encourages Islamic boarding schools to modernize by looking at the needs of "markets" that require competent human resources. There were many models of millennial Islamic boarding schools. Various developments are carried out, one of them is mastering language, entrepreneurship, ICT (Information and Communication Technology), and other current competencies. This modernization, not only have a positive impact but also problems like pesantren is harder to be able to fulfill its main function, which is to produce tafaquh fiddin people.